Nearly total optical transmission of linearly polarized light through transparent electrode composed of GaSb monolithic high-contrast grating integrated with gold - Tobing, Landobasa Yosef Mario (2022)
Achieving high transmission of light through a highly conductive structure implemented on a semiconductor remains a challenge in optoelectronics as the transmission is inevitably deteriorated by absorption and Fresnel reflection. There have been numerous efforts to design structures with near-unity transmission, yet they are typically constrained by a trade-off between conductivity and optical transmission. To address this problem, we propose and demonstrate a transmission mechanism enabled by a monolithic GaSb subwavelength grating integrated with Au stripes (metalMHCG). Near-unity transmission of polarized light is achieved by inducing low-quality factor resonance in the air gaps between the semiconductor grating stripes, which eliminates light absorption and reflection by the metal. Our numerical simulation shows 97% transmission of transverse magnetic polarized light and sheet resistance of 2.2 ωSq-1. The metalMHCG structure was realized via multiple nanopatterning and dry etching, with the largest transmission yet reported of ∼90% at a wavelength of 4.5 μm and above 75% transmission in the wavelength range from 4 to 10 μm and sheet resistance at the level of 26 ωSq-1. High optical transmission is readily achievable using any high refractive index materials employed in optoelectronics. The design of the metalMHCG is applicable in a wide electromagnetic spectrum from near ultraviolet to infrared.